Pemahaman Konsep Wahyu dalam Pendidikan Islam: Tinjauan Filsafat Ilmu - Muhammad; Primarni, Amie (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
In life, human nature is to desire happiness. How to achieve happiness in religion is clearly explained, especially in Islamic teachings. In Islamic teachings, one of the main ways to achieve happiness is through education or knowledge. This is similar to the philosophical concept of knowledge being a source of happiness. And in essence, absolute happiness is a form of someone's Absolute, Allah. Even though happiness is sometimes relative for some people, what leads to Allah is of course absolute happiness, and the indicator of this absoluteness in Islamic teachings must be based on the absolute, namely God, Allah Swt. From this, the concept of revelation from God in education, Islam in particular, has a very close connection between revelation itself and education in general. Sometimes some thoughts are unbalanced in their approach to use, resulting in an over-textualist thinking approach which places too much emphasis on revelation, and an over-rationalist thinking approach which, on the other hand, puts too much emphasis on reason. Islamic teachings moderate both. Between revelation and education. This journal was written with the main aim of being the author's effort to fulfill the assignments for the Philosophy of Science Study course taught by lecturer Dr. Amie at the IAIN Laa Roiba Postgraduate program, Bogor. The literature study is the method used in writing it. With the aim of the results to explain briefly how to understand the concept of revelation in Islamic education, review the philosophy of science, which will later conclude the importance and position between revelation and philosophical review education.